2020
DOI: 10.2147/ijn.s241756
|View full text |Cite
|
Sign up to set email alerts
|

<p>Monte Carlo Evaluation of Dose Enhancement Due to CuATSM or GNP Uptake in Hypoxic Environments with External Beam Radiation</p>

Abstract: Purpose: Most solid tumors contain areas of chronic hypoxia. Gold nanoparticles (GNP) have been extensively explored as enhancers of external beam radiation; however, GNP have lower cellular uptake in hypoxic conditions than under normoxic conditions. Conversely, the chelator diacetyl-bis (N(4)-methylthiosemicarbazonato) copper II (CuATSM) deposits copper in hypoxic regions, allowing for dose enhancement in previously inaccessible regions. Methods: External beam sources with different spectra were modeled usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…This nanocarrier system not only delivered siRNA that targeted HPV E6 gene efficiently, but inhibited xenograft tumors, which derived from HeLa cells specifically. In addition, increasing evidences showed that metallic NPs could improve radiosensitivity and attenuate systemic toxicity at the same time (Martinez et al, 2020 ; Pagáčová et al, 2019 ). Yang et al ( 2020 ) developed one biocompatible material PEGylated platinum nanoflowers (Pt NFs).…”
Section: Drug Delivery For Cervical Caner Via Nanomaterialsmentioning
confidence: 99%
“…This nanocarrier system not only delivered siRNA that targeted HPV E6 gene efficiently, but inhibited xenograft tumors, which derived from HeLa cells specifically. In addition, increasing evidences showed that metallic NPs could improve radiosensitivity and attenuate systemic toxicity at the same time (Martinez et al, 2020 ; Pagáčová et al, 2019 ). Yang et al ( 2020 ) developed one biocompatible material PEGylated platinum nanoflowers (Pt NFs).…”
Section: Drug Delivery For Cervical Caner Via Nanomaterialsmentioning
confidence: 99%